A fast-degradable environmentally friendly plastic and preparation method thereof
By treating malic acid to blend starch and polylactic acid and combining with vermiculite modification, the problems of poor compatibility and high water absorption with PLA and starch are solved, and the mechanical properties of the material are improved and the degradation rate is accelerated.
Patent Information
- Application Number
- CN202310770521.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-27
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2043-06-27
AI Technical Summary
The poor compatibility of existing PLA with starch results in poor mechanical properties and high water absorption, which cannot meet the needs of various applications.
The starch is treated with malic acid, the modified starch is blended with polylactic acid, and the mechanical properties and degradation rate of the material are improved by calcining, acidizing and modifying silane coupling agent.
It significantly improves the mechanical properties of the material, reduces water absorption, improves the degradation rate of the material, and meets the needs of rapid degradation and high performance.
Abstract
Description
Technical Field
[0001] The invention relates to the field of degradable plastics, in particular to a rapidly degradable environmentally friendly plastic and a preparation method thereof. Background Art
[0002] Polymer materials have many excellent properties that other materials do not have. They are widely used in cutting-edge technology, national defense construction and various fields of the national economy. They are indispensable and irreplaceable important materials in modern science and life. Their production and consumption have always maintained a very strong momentum. The 21st century is a new century of rapid development and full utilization of polymer materials. However, most polymer materials cannot be quickly degraded in the natural environment. The increasing amount of waste gas polymer materials has become an important source of urban garbage. The white pollution generated seriously affects the living environment of human beings. This has become a global problem. Therefore, it is very meaningful to study and develop biodegradable polymer materials.
[0003] Polymer degradation refers to the reaction of breaking the macromolecular chains that make up the polymer. The degradation process of polymers under environmental conditions such as exposure to oxygen, water, radiation, heat, light, chemical reagents, pollutants, mechanical forces and organisms (especially microorganisms) is called environmental degradation. Degradable polymer materials can be roughly divided into three types according to the degradation mechanism: photodegradable polymer materials, biodegradable polymer materials and photo-biodegradable polymer materials.
[0004] According to statistics, the annual output of natural carbohydrates containing starch in nature is 500 billion tons, which is a very large renewable resource library. As a renewable resource, starch was originally used only as an inert extender and flame retardant to reduce costs in polyurethane formulations. However, due to the oil crisis and a series of environmental problems, its use in the field of degradable materials has attracted widespread attention today, which also indicates the broad prospects of starch-based biodegradable plastics. However, all-starch thermoplastics have poor mechanical properties and are very sensitive to environmental humidity, and cannot meet most application requirements. Therefore, improving the mechanical properties and water resistance of all-starch thermoplastics has become an important research direction for the development of high-performance, fast-degradable, environmentally friendly plastics.
[0005] Polylactic acid (PLA) is polymerized from lactic acid monomers, also known as poly(acrylonitrile), and can be converted from starch using special bacteria. PLA has good biocompatibility and mechanical properties, and has been widely used as a medical polymer material, used as a bone fixation material, drug release system, etc. However, as biodegradable materials have gradually become a research hotspot in recent years, the development and application of PLA has also begun to turn to various application fields such as plastic packaging and textiles. Blending PLA with starch can greatly reduce costs while ensuring its good biodegradability. However, existing studies have shown that PLA has poor compatibility with starch, and when the starch content is greater than 60%, the water absorption of the blend will increase rapidly. Therefore, new means are needed to solve the problem of poor compatibility between PLA and starch and its water absorption.
[0006] CN 106221157 A discloses a biodegradable polylactic acid film and a preparation method thereof, wherein polylactic acid is used as the main raw material, kaolin and vermiculite powder are used as bioactive agents, polylactic acid, polybutylene carbonate, polyethylene, starch, zinc stearate, magnesium oxide, vermiculite powder, kaolin, plasticizer and phosphite are added into a mixer, the heating temperature is 70-90°C, the rotation speed is 180r / min, the time is 10-20min, and the mixing is uniformly stirred to obtain a biodegradable polylactic acid film. Directly adding vermiculite powder and kaolin has poor compatibility between vermiculite powder and polylactic acid, starch and polylactic acid, which greatly affects the mechanical properties and water resistance of the material, so it is necessary to improve this. Summary of the invention
[0007] To achieve the above object, the present invention provides a rapidly degradable environmentally friendly plastic and a preparation method thereof.
[0008] A fast-degradable environmentally friendly plastic comprises the following components by weight: 50 parts of polylactic acid, 50 parts of modified starch, 20 parts of silane coupling agent-modified vermiculite, and 0.5 parts of an antioxidant.
[0009] The preparation method of the silane coupling agent modified vermiculite comprises the following steps:
[0010] S1: clean the vermiculite, drain it, calcine it at 1100-1300℃ for 0.5-2h, and crush it into 10-50μm to obtain expanded vermiculite powder;
[0011] S2: Mix the expanded vermiculite powder obtained in S1 and 1-2 mol / L hydrochloric acid in a bath ratio of 1 g: (10-20) mL, and reflux for reaction at 90-100° C. for 1-2 h. After the reaction stops, filter out the precipitate, wash it to neutrality, and dry it to obtain acidified vermiculite.
[0012] S3, by mass, adds 15-25 parts of vinyltrimethoxysilane to 75-85 parts of an alcohol aqueous solution with an alcohol content of 75-85wt%, and stirs to fully hydrolyze it; secondly, adds 5-15 parts of the acidified vermiculite prepared in S2 to the above solution under stirring, stirs for 1-2h, filters out the precipitate, and dries it at 110-130°C for 1-2h to obtain silane coupling agent modified vermiculite.
[0013] A method for preparing a rapidly degradable environmentally friendly plastic comprises the following steps:
[0014] (1) drying starch at 100-130° C. for 8-10 hours to obtain dried starch; drying polylactic acid at 40-45° C. for 10-12 hours to obtain dried polylactic acid;
[0015] (2) mixing 95-99 wt % of the dried starch obtained in step (1) and 1-5 wt % of malic acid, melting, mixing and extruding the mixture using a twin-screw extruder, and cooling the mixture to obtain modified starch;
[0016] (3) By weight, 40-60 parts of the dried polylactic acid obtained in step (1), 40-60 parts of the modified starch obtained in step (2), 10-30 parts of silane coupling agent-modified vermiculite, and 0.1-1 part of an antioxidant are added to a torque rheometer and mixed, and then transferred to a flat-plate vulcanizer for preheating, pressing, and cooling to obtain the rapidly degradable environmentally friendly plastic.
[0017] The starch in step (1) is at least one of corn starch, wheat starch and tapioca starch; preferably, the starch is corn starch.
[0018] The parameters of the twin-screw extruder in step (2) are set to a screw speed of 280-340 r / min, a feeding rate of 28-34 r / min, a conveyor belt speed of 60-70 r / min, a conveying section temperature of 96-100°C, a melting section temperature of 130-140°C, a homogenizing section temperature of 148-152°C, and an extrusion melt pressure of 26-30 MPa.
[0019] The torque rheometer mixing conditions in step (3) are: 160-180° C., 100-160 r / min, 4-10 min.
[0020] The pressing plate forming conditions in step (3) are: temperature 170-190° C., pressure 9-11 MPa, preheating 2-4 min, hot pressing 2-3 min, cooling 2-4 min, and cold pressing 2-3 min.
[0021] The antioxidant in step (3) is at least one of antioxidant 1010, antioxidant 1076, antioxidant 168, and antioxidant TNP; preferably, the antioxidant is antioxidant 168.
[0022] The mechanical properties of the environmentally friendly plastic obtained by directly compounding polylactic acid and starch are poor, and the water absorption rate is high. This is because starch and polylactic acid are hydrophilic and hydrophobic, respectively, and the interface of the blend is incompatible, so the mechanical properties are poor, and the starch material has high water absorption. When its specific gravity is large, the water absorption rate of the material will increase significantly. Therefore, the present invention first uses malic acid to treat starch, and the mechanical properties of the environmentally friendly plastic obtained by rapid degradation are significantly improved and the water absorption rate is significantly reduced. This is because malic acid can promote starch acidolysis, improve the plasticizing effect of starch, and reduce starch viscosity, so that its dispersed phase size is smaller and more evenly distributed in polylactic acid.
[0023] Further, but its water absorption also slightly increases. The present invention adds vermiculite powder thereto, as a kind of nano material, it has a larger space gap, a smaller grain size and a larger specific surface area, and its high surface energy causes the stability of the surface atoms of the particles to deteriorate, thereby producing surface and interface effects, and can be well combined with starch, and improve its mechanical properties. However, the particle size is small, the number of atoms on the surface is large, its surface energy is high, and the adsorption effect is strong, and each particle is easily reunited with each other, and it is impossible to be well dispersed in the polymer matrix; the particle surface is hydrophilic and oleophobic, and the affinity with starch is good, but the interfacial bonding force with polylactic acid is weak, and when impacted by external force, it is easy to cause interface defects, resulting in a decrease in material performance, and vermiculite powder is very easy to reunite in starch, which greatly limits the promotion of vermiculite powder for material mechanical properties. Therefore, the present invention further converts vermiculite into expanded vermiculite by calcining. The rapidly expanded volume allows a large number of pores to exist in the expanded vermiculite. On the one hand, starch and polylactic acid can invade the expanded vermiculite powder to form a tighter combination. On the other hand, the adsorption of water molecules by the expanded vermiculite powder is enhanced. During the high-temperature smelting process, the hydrogen bonding effect of water molecules in the starch is further reduced, so that the starch is dispersed into smaller molecular clusters, thereby promoting the fusion of polylactic acid and starch.
[0024] It is found from the existing literature that acid-treated vermiculite also has the effect of enlarging pore size and improving the surface area of vermiculite. Therefore, the present invention adopts acid-treated expanded vermiculite powder, and is applied to starch-polylactic acid composite material, and finds that the mechanical properties of the environmentally friendly plastic obtained by rapid degradation are further improved, but the degree of improvement is not as good as that of embodiment 4 by using expanded vermiculite. Therefore, the present invention speculates that acid treatment of expanded vermiculite powder can further improve the mechanical properties of the material, and the present invention adopts the mode of acid treatment of expanded vermiculite powder, and finds that the mechanical properties of the environmentally friendly plastic finally obtained by rapid degradation are further improved, and the present invention believes that this is due to the combination of expansion treatment and acid treatment, which is more conducive to expanding the surface pore size of vermiculite and improving its specific surface area, promoting the dispersion and affinity of vermiculite in starch-polylactic acid system. In addition, acid treatment has replaced the water molecules between some vermiculite molecular layers, improved the hydrophilicity of vermiculite, and is conducive to reducing the water absorption rate of material. Furthermore, in order to further improve the affinity between vermiculite powder and polylactic acid, the present invention further modifies the acid-treated expanded vermiculite powder with a silane coupling agent to enhance its organic affinity and further enhance the hydrophobicity of the material, thereby obtaining an environmentally friendly plastic with excellent mechanical properties and low water absorption and rapid degradation.
[0025] In addition, after the starch is treated with acid, its molecules are acid-hydrolyzed, the molecular weight is reduced, and it is easier to degrade. A large amount of inorganic material vermiculite is added to the material, which decomposes slowly in the soil, thereby slowing down the decomposition rate of the material. The water absorption of the calcined vermiculite is improved after expansion, so that the obtained fast-degradable environmentally friendly plastic is relatively moist, which is conducive to the decomposition of the plastic. The acidification treatment will also form a large number of active sites on the surface of the vermiculite, which has a certain catalytic degradation ability and can accelerate the degradation of the plastic. After modification with a silane coupling agent, the degradation rate of the material is further improved. The present invention believes that this is because after the silane coupling agent treatment, its affinity with polylactic acid is further enhanced, which is conducive to promoting the decomposition of polylactic acid, thereby accelerating the decomposition rate, so that the fast-degradable environmentally friendly plastic prepared by the present invention has an extremely fast natural degradation rate.
[0026] Beneficial effects of the present invention:
[0027] The present invention produces a fast-degradable environmentally friendly plastic, which uses starch and polylactic acid as a composite substrate, and uses vermiculite as an auxiliary agent to promote the affinity of the two materials. Furthermore, the present invention calcines and acidifies the vermiculite, thereby enhancing the affinity of the vermiculite to polylactic acid and its dispersibility in the starch polylactic acid system, greatly improving the mechanical properties of the obtained fast-degradable environmentally friendly plastic, and reducing its water absorption, which can reduce the problems of mildew, breakage, etc. of the plastic during use, thereby increasing its practicality and expanding its scope of use.
[0028] In addition, the fast-degradable environmentally friendly plastic prepared by the present invention reduces the amount of polylactic acid used, and when the polylactic acid content is less than 50wt%, it still has excellent mechanical properties and low water absorption, greatly saving its cost. Its faster degradation rate also meets the existing environmental protection theme. DETAILED DESCRIPTION
[0029] Corn starch, product number: xx135412, Shanghai Yuyuan Biochemistry Co., Ltd.
[0030] Polylactic acid, product number: XY30789, Shanghai Xuanya Biotechnology Co., Ltd.
[0031] Antioxidant 168, CAS: 31570-04-4.
[0032] Example 1
[0033] A method for preparing a rapidly degradable environmentally friendly plastic comprises the following steps:
[0034] (1) drying starch at 120° C. for 10 hours to obtain dried starch; drying polylactic acid at 45° C. for 12 hours to obtain dried polylactic acid;
[0035] (2) By weight, 50 parts of the dried polylactic acid obtained in step (1), 50 parts of the dried starch obtained in step (1), and 0.5 parts of an antioxidant are added to a torque rheometer and mixed, and then transferred to a flat-plate vulcanizer for preheating, pressing, cooling and shaping to obtain the rapidly degradable environmentally friendly plastic.
[0036] The starch in step (1) is corn starch.
[0037] The torque rheometer mixing conditions in step (2) are: 170° C., 120 r / min, 5 min.
[0038] The pressing plate forming conditions in step (2) are: temperature 180° C., pressure 10 MPa, preheating for 3 min, hot pressing for 2 min, cooling for 3 min, and cold pressing for 2 min.
[0039] The antioxidant in step (2) is antioxidant 168.
[0040] Example 2
[0041] A method for preparing a rapidly degradable environmentally friendly plastic comprises the following steps:
[0042] (1) drying starch at 120° C. for 10 hours to obtain dried starch; drying polylactic acid at 45° C. for 12 hours to obtain dried polylactic acid;
[0043] (2) mixing 98 wt % of the dried starch obtained in step (1) and 2 wt % of malic acid, melting, mixing and extruding the mixture using a twin-screw extruder, and cooling the mixture to obtain modified starch;
[0044] (3) By weight, 50 parts of the dried polylactic acid obtained in step (1), 50 parts of the modified starch obtained in step (2), and 0.5 parts of an antioxidant are added to a torque rheometer and mixed, and then transferred to a flat-plate vulcanizer for preheating, pressing, and cooling to obtain the rapidly degradable environmentally friendly plastic.
[0045] The starch in step (1) is corn starch.
[0046] The parameters of the twin-screw extruder in step (2) are set as follows: screw speed of 300 r / min, feeding rate of 30 r / min, conveyor belt speed of 65 r / min, conveying section temperature of 98 ° C, melting section temperature of 136 ° C, homogenizing section temperature of 151 ° C, and extrusion melt pressure of 28 MPa.
[0047] The torque rheometer mixing conditions in step (3) are: 170° C., 120 r / min, 5 min.
[0048] The pressing plate forming conditions in step (3) are: temperature 180°C, pressure 10 MPa, preheating for 3 min, hot pressing for 2 min, cooling for 3 min, and cold pressing for 2 min.
[0049] The antioxidant in step (3) is antioxidant 168.
[0050] Example 3
[0051] A method for preparing a rapidly degradable environmentally friendly plastic comprises the following steps:
[0052] (1) drying starch at 120° C. for 10 hours to obtain dried starch; drying polylactic acid at 45° C. for 12 hours to obtain dried polylactic acid;
[0053] (2) mixing 98 wt % of the dried starch obtained in step (1) and 2 wt % of malic acid, melting, mixing and extruding the mixture using a twin-screw extruder, and cooling the mixture to obtain modified starch;
[0054] (3) By weight, 50 parts of the dried polylactic acid obtained in step (1), 50 parts of the modified starch obtained in step (2), 20 parts of vermiculite powder, and 0.5 parts of an antioxidant are added to a torque rheometer and mixed, and then transferred to a flat-plate vulcanizer for preheating, pressing, and cooling to obtain the rapidly degradable environmentally friendly plastic.
[0055] The starch in step (1) is corn starch.
[0056] The parameters of the twin-screw extruder in step (2) are set as follows: screw speed of 300 r / min, feeding rate of 30 r / min, conveyor belt speed of 65 r / min, conveying section temperature of 98 ° C, melting section temperature of 136 ° C, homogenizing section temperature of 151 ° C, and extrusion melt pressure of 28 MPa.
[0057] The torque rheometer mixing conditions in step (3) are: 170° C., 120 r / min, 5 min.
[0058] The pressing plate forming conditions in step (3) are: temperature 180°C, pressure 10 MPa, preheating for 3 min, hot pressing for 2 min, cooling for 3 min, and cold pressing for 2 min.
[0059] The antioxidant in step (3) is antioxidant 168.
[0060] The method for preparing the vermiculite powder in step (3) comprises the following steps: cleaning the vermiculite, draining it and crushing it to 50 μm to obtain the vermiculite powder.
[0061] Example 4
[0062] A method for preparing a rapidly degradable environmentally friendly plastic comprises the following steps:
[0063] (1) drying starch at 120° C. for 10 hours to obtain dried starch; drying polylactic acid at 45° C. for 12 hours to obtain dried polylactic acid;
[0064] (2) mixing 98 wt % of the dried starch obtained in step (1) and 2 wt % of malic acid, melting, mixing and extruding the mixture using a twin-screw extruder, and cooling the mixture to obtain modified starch;
[0065] (3) By weight, 50 parts of the dried polylactic acid obtained in step (1), 50 parts of the modified starch obtained in step (2), 20 parts of expanded vermiculite powder, and 0.5 parts of an antioxidant are added to a torque rheometer for mixing, and then transferred to a flat-plate vulcanizer for preheating, pressing, and cooling to obtain the rapidly degradable environmentally friendly plastic.
[0066] The starch in step (1) is corn starch.
[0067] The parameters of the twin-screw extruder in step (2) are set as follows: screw speed of 300 r / min, feeding rate of 30 r / min, conveyor belt speed of 65 r / min, conveying section temperature of 98 ° C, melting section temperature of 136 ° C, homogenizing section temperature of 151 ° C, and extrusion melt pressure of 28 MPa.
[0068] The torque rheometer mixing conditions in step (3) are: 170° C., 120 r / min, 5 min.
[0069] The pressing plate forming conditions in step (3) are: temperature 180°C, pressure 10 MPa, preheating for 3 min, hot pressing for 2 min, cooling for 3 min, and cold pressing for 2 min.
[0070] The antioxidant in step (3) is antioxidant 168.
[0071] The method for preparing the expanded vermiculite powder in step (3) comprises the following steps: cleaning the vermiculite, draining it, calcining it at 1100° C. for 1 hour, and crushing it to 50 μm to obtain the expanded vermiculite powder.
[0072] Example 5
[0073] A method for preparing a rapidly degradable environmentally friendly plastic comprises the following steps:
[0074] (1) drying starch at 120° C. for 10 hours to obtain dried starch; drying polylactic acid at 45° C. for 12 hours to obtain dried polylactic acid;
[0075] (2) mixing 98 wt % of the dried starch obtained in step (1) and 2 wt % of malic acid, melting, mixing and extruding the mixture using a twin-screw extruder, and cooling the mixture to obtain modified starch;
[0076] (3) By weight, 50 parts of the dried polylactic acid obtained in step (1), 50 parts of the modified starch obtained in step (2), 20 parts of acidified vermiculite, and 0.5 parts of an antioxidant are added to a torque rheometer and mixed, and then transferred to a flat-plate vulcanizer for preheating, pressing, and cooling to obtain the rapidly degradable environmentally friendly plastic.
[0077] The starch in step (1) is corn starch.
[0078] The parameters of the twin-screw extruder in step (2) are set as follows: screw speed of 300 r / min, feeding rate of 30 r / min, conveyor belt speed of 65 r / min, conveying section temperature of 98 ° C, melting section temperature of 136 ° C, homogenizing section temperature of 151 ° C, and extrusion melt pressure of 28 MPa.
[0079] The torque rheometer mixing conditions in step (3) are: 170° C., 120 r / min, 5 min.
[0080] The pressing plate forming conditions in step (3) are: temperature 180°C, pressure 10 MPa, preheating for 3 min, hot pressing for 2 min, cooling for 3 min, and cold pressing for 2 min.
[0081] The antioxidant in step (3) is antioxidant 168.
[0082] The preparation method of the acidified vermiculite described in step (3) comprises the following steps:
[0083] S1: clean the vermiculite, drain it and grind it into 50 μm to obtain vermiculite powder;
[0084] S2: The vermiculite powder prepared in S1 is mixed with 2 mol / L hydrochloric acid in a bath ratio of 1 g:10 mL, and refluxed at 95° C. for 2 h. After the reaction stops, the precipitate is filtered out, washed to neutrality, and dried to obtain acidified vermiculite.
[0085] Example 6
[0086] A method for preparing a rapidly degradable environmentally friendly plastic comprises the following steps:
[0087] (1) drying starch at 120° C. for 10 hours to obtain dried starch; drying polylactic acid at 45° C. for 12 hours to obtain dried polylactic acid;
[0088] (2) mixing 98 wt % of the dried starch obtained in step (1) and 2 wt % of malic acid, melting, mixing and extruding the mixture using a twin-screw extruder, and cooling the mixture to obtain modified starch;
[0089] (3) By weight, 50 parts of the dried polylactic acid obtained in step (1), 50 parts of the modified starch obtained in step (2), 20 parts of acidified vermiculite, and 0.5 parts of an antioxidant are added to a torque rheometer and mixed, and then transferred to a flat-plate vulcanizer for preheating, pressing, and cooling to obtain the rapidly degradable environmentally friendly plastic.
[0090] The starch in step (1) is corn starch.
[0091] The parameters of the twin-screw extruder in step (2) are set as follows: screw speed of 300 r / min, feeding rate of 30 r / min, conveyor belt speed of 65 r / min, conveying section temperature of 98 ° C, melting section temperature of 136 ° C, homogenizing section temperature of 151 ° C, and extrusion melt pressure of 28 MPa.
[0092] The torque rheometer mixing conditions in step (3) are: 170° C., 120 r / min, 5 min.
[0093] The pressing plate forming conditions in step (3) are: temperature 180°C, pressure 10 MPa, preheating for 3 min, hot pressing for 2 min, cooling for 3 min, and cold pressing for 2 min.
[0094] The antioxidant in step (3) is antioxidant 168.
[0095] The preparation method of the acidified vermiculite described in step (3) comprises the following steps:
[0096] S1: clean the vermiculite, drain it, calcine it at 1100℃ for 1h, and grind it into 50μm to obtain expanded vermiculite powder;
[0097] S2: Mix the expanded vermiculite powder obtained in S1 and 2 mol / L hydrochloric acid in a bath ratio of 1 g:10 mL, reflux at 95° C. for 2 h, filter and collect the precipitate after the reaction stops, wash to neutrality, and dry to obtain acidified vermiculite.
[0098] Example 7
[0099] A method for preparing a rapidly degradable environmentally friendly plastic comprises the following steps:
[0100] (1) drying starch at 120° C. for 10 hours to obtain dried starch; drying polylactic acid at 45° C. for 12 hours to obtain dried polylactic acid;
[0101] (2) mixing 98 wt % of the dried starch obtained in step (1) and 2 wt % of malic acid, melting, mixing and extruding the mixture using a twin-screw extruder, and cooling the mixture to obtain modified starch;
[0102] (3) By weight, 50 parts of the dried polylactic acid obtained in step (1), 50 parts of the modified starch obtained in step (2), 20 parts of silane coupling agent-modified vermiculite, and 0.5 parts of an antioxidant are added to a torque rheometer and mixed, and then transferred to a flat-plate vulcanizer for preheating, pressing, and cooling to obtain the rapidly degradable environmentally friendly plastic.
[0103] The starch in step (1) is corn starch.
[0104] The parameters of the twin-screw extruder in step (2) are set as follows: screw speed of 300 r / min, feeding rate of 30 r / min, conveyor belt speed of 65 r / min, conveying section temperature of 98 ° C, melting section temperature of 136 ° C, homogenizing section temperature of 151 ° C, and extrusion melt pressure of 28 MPa.
[0105] The torque rheometer mixing conditions in step (3) are: 170° C., 120 r / min, 5 min.
[0106] The pressing plate forming conditions in step (3) are: temperature 180°C, pressure 10 MPa, preheating for 3 min, hot pressing for 2 min, cooling for 3 min, and cold pressing for 2 min.
[0107] The antioxidant in step (3) is antioxidant 168.
[0108] The method for preparing the silane coupling agent modified vermiculite in step (3) comprises the following steps:
[0109] S1: clean the vermiculite, drain it, calcine it at 1100℃ for 1h, and grind it into 50μm to obtain expanded vermiculite powder;
[0110] S2: the expanded vermiculite powder prepared in S1 is mixed with 2 mol / L hydrochloric acid in a bath ratio of 1 g: 10 mL, and refluxed at 95°C for 2 h. After the reaction stops, the precipitate is filtered out, washed to neutrality, and dried to obtain acidified vermiculite.
[0111] S3, by mass, adds 20 parts of vinyltrimethoxysilane to 80 parts of an alcohol aqueous solution with an alcohol content of 80wt%, and stirs to fully hydrolyze it; secondly, adds 10 parts of acidified vermiculite obtained in S2 to the above solution under stirring, stirs for 1 hour, filters out the precipitate, and dries it at 130°C for 1 hour to obtain silane coupling agent modified vermiculite.
[0112] Test Example 1
[0113] The rapidly degradable environmentally friendly plastics prepared in Examples 1 to 7 of the present invention were tested with reference to GB / T 1040.3-2006 “Determination of tensile properties of plastics Part 3: Test conditions for films and sheets”.
[0114] Water absorption rate: According to GB / T 1034-2008 "Determination of water absorption of plastics", the test was carried out. At room temperature, the fast-degradable environmentally friendly plastic prepared in the embodiment was placed at 85°C for drying, weighed m0, and then immersed in water for 24 hours. After being taken out, the surface moisture was absorbed with filter paper and weighed m1. The water absorption rate was calculated as (m1-m0) / m0×100%. Five test samples were taken and the final result was averaged.
[0115] Specimen size: 20mm wide, 150mm long, 0.8mm thick.
[0116] Test conditions: temperature 25°C, relative humidity 50%, stretching rate 5 mm / min, inlet force: 0.5N.
[0117] Testing instrument: universal mechanical testing machine.
[0118] Table 1: Tensile strength test results
[0119] Tensile strength(MPa) Elongation at break / % Water absorption / % Example 1 21 39 9.6 Example 2 26 58 6.4 Example 3 31 77 6.8 Example 4 37 102 7.4 Example 5 33 82 6.7 Example 6 42 136 5.6 Example 7 46 154 4.0
[0120] It can be seen from Table 1 that Example 1 uses polylactic acid and starch to directly compound, and the obtained rapidly degradable environmentally friendly plastic has poor mechanical properties and high water absorption. This is because starch and polylactic acid are hydrophilic and hydrophobic, respectively, and the interface of the blend is incompatible, so its mechanical properties are poor, and the starch material has high water absorption. When its specific gravity is large, the water absorption rate of the material will increase significantly.
[0121] In Example 2, malic acid is first used to treat starch, and the mechanical properties of the obtained rapidly degradable environmentally friendly plastic are significantly improved and the water absorption rate is significantly reduced. This is because malic acid can promote the acidolysis of starch, improve the plasticization effect of starch, and reduce the viscosity of starch, making its dispersed phase size smaller and more evenly distributed in polylactic acid.
[0122] The mechanical property of the environmentally friendly plastic of rapid degradation obtained by embodiment 3 is further improved than embodiment 2, but its water absorption also slightly rises. This is due to adding vermiculite powder therein, as a kind of nano material, it has larger space gap, smaller grain size and larger specific surface area, and its high surface energy causes the stability of particle surface atoms to deteriorate, thereby producing surface and interface effect, can be well combined with starch, improve its mechanical property. However, active groups such as hydroxyl are ubiquitous on the vermiculite surface, affecting its affinity with polylactic acid, and the vermiculite of smaller particle size also exists the phenomenon of easy aggregation, especially in starch and polylactic acid composite material, due to the weaker affinity with polylactic acid, vermiculite powder is very easy to reunite in starch, greatly limiting the promotion of vermiculite powder for material mechanical properties. Therefore, in Example 4, the vermiculite is further converted into expanded vermiculite by calcining. The rapidly expanded volume allows a large number of pores to exist in the expanded vermiculite. On the one hand, starch and polylactic acid can invade the interior of the expanded vermiculite powder to form a tighter combination. On the other hand, the adsorption of water molecules by the expanded vermiculite powder is enhanced. During the high-temperature smelting process, the hydrogen bonding of water molecules in the starch is further reduced, so that the starch is dispersed into smaller molecular clusters, thereby promoting the fusion of polylactic acid and starch.
[0123] It is found from existing literature that acid-treated vermiculite also has the effect of enlarging pore size and improving the surface area of vermiculite. Therefore, embodiment 5 The present invention adopts acid-treated vermiculite powder, and applies it to starch-polylactic acid composite material, and finds that the mechanical properties of the environmentally friendly plastic obtained by rapid degradation are improved by simply adopting vermiculite in embodiment 3, but the degree of improvement is not as good as that of expanded vermiculite in embodiment 4. Therefore, the present invention speculates that acid treatment of expanded vermiculite powder can further improve the mechanical properties of the material, and the present invention adopts the mode of acid treatment of expanded vermiculite powder in embodiment 6, and finds that the mechanical properties of the environmentally friendly plastic finally obtained by rapid degradation have more obvious improvement than embodiment 4 and embodiment 5, and the present invention believes that this is due to the combination of expansion treatment and acid treatment, which is more conducive to expanding the surface pore size of vermiculite and improving its specific surface area, promoting the dispersion and affinity of vermiculite in starch-polylactic acid system. In addition, acid treatment replaces the water molecules between some vermiculite molecular layers, improves the hydrophilicity of vermiculite, and is conducive to reducing the water absorption rate of the material. Furthermore, in order to further improve the affinity between vermiculite powder and polylactic acid, the acid-treated expanded vermiculite powder in Example 7 is further modified with a silane coupling agent to enhance its organic affinity and further enhance the hydrophobicity of the material, thereby obtaining an environmentally friendly plastic with excellent mechanical properties and low water absorption and rapid degradation.
[0124] Test Example 2
[0125] Degradability test
[0126] Soil burial method: The sieved soil is placed in a wide-mouth bottle, and the fast-degradable environmentally friendly plastic prepared in Examples 1-7 of the present invention is buried in the soil in parallel. The wide-mouth bottle is placed in a constant temperature box, taken out after 30 days, immersed in a 75% ethanol solution for rinsing, and then washed once with deionized water. After drying, the mass is recorded and the mass loss is detected.
[0127] Table 2: Degradability test results
[0128] Mass loss of soil buried for 30 days / % Example 1 34.1 Example 2 41.7 Example 3 37.1 Example 4 41.6 Example 5 42.2 Example 6 49.1 Example 7 54.2
[0129] As can be seen from Table 2, Example 1 simply uses polylactic acid and starch to compound, and the degradation rate of the rapidly degradable environmentally friendly plastic obtained in the soil is relatively slow, while in Example 2, after the starch is treated with acid, its molecules are acidified, the molecular weight is reduced, and it is easier to degrade. In Example 3, due to the addition of a large amount of inorganic material vermiculite in the material, it decomposes slowly in the soil, thereby slowing down the decomposition rate of the material. In Example 4, the water absorption of vermiculite is improved after expansion, so that the rapidly degradable environmentally friendly plastic obtained is relatively moist, which is conducive to its decomposition. In Example 5, the vermiculite is acidified, and a large number of active sites will be formed on the surface of the vermiculite, which has a certain catalytic degradation ability and can accelerate the degradation of plastics. Example 6 adopts the method of acidifying the expanded vermiculite powder, combining the advantages of both Example 4 and Example 5, and its degradation rate is further accelerated. After Example 7 is modified with a silane coupling agent, the degradation rate of the material is further improved. The present invention believes that this is because after the silane coupling agent is treated, its affinity with polylactic acid is further strengthened, which is conducive to promoting the decomposition of polylactic acid, thereby accelerating the decomposition rate.
Claims
1. A method for preparing a rapidly degradable environmentally friendly plastic, characterized in that: The following steps are involved: (1) drying starch at 100-130° C. for 8-10 hours to obtain dried starch; drying polylactic acid at 40-45° C. for 10-12 hours to obtain dried polylactic acid; (2) mixing 95-99 wt % of the dried starch obtained in step (1) and 1-5 wt % of malic acid, melting, mixing and extruding the mixture using a twin-screw extruder, and cooling the mixture to obtain modified starch; (3) adding 40-60 parts by mass of the dried polylactic acid obtained in step (1), 40-60 parts of the modified starch obtained in step (2), 10-30 parts of silane coupling agent-modified vermiculite, and 0.1-1 parts of an antioxidant into a torque rheometer for mixing, and then transferring the mixture into a flat-plate vulcanizing machine for preheating, pressing, and cooling to obtain the rapidly degradable environmentally friendly plastic; The preparation method of the silane coupling agent modified vermiculite comprises the following steps: S1: clean the vermiculite, drain it, calcine it at 1100-1300℃ for 0.5-2h, and crush it into 10-50μm to obtain expanded vermiculite powder; S2: Mix the expanded vermiculite powder obtained in S1 with 1-2 mol / L hydrochloric acid in a bath ratio of 1g: (10-20) mL, reflux reaction at 90-100°C for 1-2h, filter and collect the precipitate after the reaction stops, wash and dry to obtain acidified vermiculite; S3, by mass, adds 15-25 parts of vinyltrimethoxysilane to 75-85 parts of an alcohol aqueous solution with an alcohol content of 75-85wt%, and stirs to fully hydrolyze it; secondly, adds 5-15 parts of the acidified vermiculite prepared in S2 to the above solution under stirring, stirs for 1-2h, filters out the precipitate, and dries it at 110-130°C for 1-2h to obtain silane coupling agent modified vermiculite.
2. The method for preparing the rapidly degradable environmentally friendly plastic according to claim 1, characterized in that: The starch in step (1) is at least one of corn starch, wheat starch and tapioca starch.
3. The method for preparing the rapidly degradable environmentally friendly plastic according to claim 1, characterized in that: The parameters of the twin-screw extruder in step (2) are set to a screw speed of 280-340 r / min, a feeding rate of 28-34 r / min, a conveyor belt speed of 60-70 r / min, a conveying section temperature of 96-100°C, a melting section temperature of 130-140°C, a homogenizing section temperature of 148-152°C, and an extrusion melt pressure of 26-30 MPa.
4. The method for preparing the rapidly degradable environmentally friendly plastic according to claim 1, characterized in that: The torque rheometer mixing conditions in step (3) are: 160-180° C., 100-160 r / min, 4-10 min.
5. The method for preparing the rapidly degradable environmentally friendly plastic according to claim 1, characterized in that: The pressing plate forming conditions in step (3) are: temperature 170-190° C., pressure 9-11 MPa, preheating 2-4 min, hot pressing 2-3 min, cooling 2-4 min, and cold pressing 2-3 min.
6. The method for preparing the rapidly degradable environmentally friendly plastic according to claim 1, characterized in that: The antioxidant in step (3) is at least one of antioxidant 1010, antioxidant 1076, antioxidant 168, and antioxidant TNP.
7. A rapidly degradable environmentally friendly plastic, characterized in that: The fast-degradable environmentally friendly plastic is prepared by the preparation method of any one of claims 1 to 6.
Citation Information
Patent Citations
Biodegradable polylactic acid film and preparation method thereof
CN106221157A
Starch-based biodegradable material and its preparation method
CN1354196A